The Effect of Target Achievement Rewards on the Performance of Employees at BMT UGT Sidogiri Klampis Branch - Tamimah Tamimah; Dainori Dainori; Hanik Mariatul Amri (Journal of Economics and Social Sciences (JESS), 2025)
The purpose of this study is to determine the effect of target achievement rewards on employee performance, both partially and simultaneously. The research method used is quantitative research, with the population being all employees at BMT UGT Sidogiri. The sample selection used random sampling. Data collection techniques used questionnaires and Google forms. The analysis tools used were instrument testing (validity testing, reliability testing), classical assumptions (normality testing), and hypothesis testing (simple linear regression analysis, T-test, and F-test). The results of the study indicate that target achievement rewards have a positive and significant effect on the performance of BMT UGT Sidogiri Klampis Branch employees, both partially and simultaneously.